Level of Survivin in Breast Cancer Patients Serum - Irmayanti, -; U, Bahrun; I D, Kartika; F, Irsandy; A T, Sanna (International Journal of Human and Health Sciences (IJHHS), 2024)
Objectives: The progressivity of breast cancer is controlled by a balance between cell proliferation and apoptosis. Dysregulation of apoptotic pathways leading to disorders such as cancer, autoimmune, and immunodeficiency diseases, as well as neurodegenerative disorders. Cancer cells be resistant to apoptosis by expressing an anti-apoptotic protein i.e. Apoptosis Protein Inhibitor (IAP). Survivin is an apoptotic inhibitor protein (IAP) that selectively plays a role in cancer cells, inhibits apoptosis, promotes cell division and improves angiogenesis. Detection of survivin in the blood can serve as an ideal marker for cancer diagnosis and detection. This study aims to determine the levels of survivin in breast cancer and its role as a marker of breast cancer. Methods: A cross-sectional method was conducted in Dr. Wahidin Sudirohusodo Hospital Makassar and Hasanuddin University Academic Hospital during the period from July to August 2017. There were 72 subjects (20 control, 26 non-metastatic breast cancer and 26 metastatic breast cancer), with age range of 30-61 years. The survivin test using human survivin kit with enzyme linked immunosorbent assay method (ELISA). Results: The results showed that serum surviving level in breast cancer group was significantly higher than control group (p=0,000), also higher in the metastasis group than in non-metastatic, but statistically not significant (p=0,147). Conclusion: Survivin level serum in breast cancer patients was increase. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S57